KARAKTERISTIK PETERNAK DAN MANAJEMEN PEMELIHARAAN BABI LOKAL DI KECAMATAN ALAK KOTA KUPANG - Redempta Wea (Politeknik Pertanian Negeri Kupang, 2008)
This study was carried out from July to September 2005, to obtain the description or data base on local pig farming at Alak Subdistrict, Kupang City. The method of the research used direct interview to 30 respondents and direct field observation. The results showed that the breeder characteristic at Alak Subdistrict, in the case of prime work, the breeders were enterpreneur; their conservancy experience was 6-10 year; numbers of family member in concerned were 4 people, average of age was 47,7 years old; education level was 66,6% under SLTP; pig ownership was 3 tail; purpose of pig conservancy was used as saving 96,7%, and conservancy systems were extensive 36,7%, flourishing intensive 16,7%, and intensive 46,7%. Therefore, conducting the demplot of pig conservancy, local feed, cage pattern, intensive counseling and use of technology by participative approach.Keyword: Breeder Characteristic, conservancy management, Local Pig, Kota Kupang